A single‐cell RNA expression atlas of normal, preneoplastic and tumorigenic states in the human breast - Pal, Bhupinder; Chen, Yunshun; Vaillant, François; Capaldo, Bianca D; Joyce, Rachel; Song, Xiaoyu; Bryant, Vanessa L; Penington, Jocelyn S; Di Stefano, Leon; Tubau Ribera, Nina; Wilcox, Stephen; Mann, Gregory B; et al. (The EMBO journal, 2021)
To examine global changes in breast heterogeneity across different states, we determined the single‐cell transcriptomes of > 340,000 cells encompassing normal breast, preneoplastic BRCA1 +/– tissue, the major breast cancer subtypes, and pairs of tumors and involved lymph nodes. Elucidation of the normal breast microenvironment revealed striking changes in the stroma of post‐menopausal women. Single‐cell profiling of 34 treatment‐naive primary tumors, including estrogen receptor (ER) + , HER2 + , and triple‐negative breast cancers, revealed comparable diversity among cancer cells and a discrete subset of cycling cells. The transcriptomes of preneoplastic BRCA1 +/– tissue versus tumors highlighted global changes in the immune microenvironment. Within the tumor immune landscape, proliferative CD8 + T cells characterized triple‐negative and HER2 + cancers but not ER + tumors, while all subtypes comprised cycling tumor‐associated macrophages, thus invoking potentially different immunotherapy targets. Copy number analysis of paired ER + tumors and lymph nodes indicated seeding by genetically distinct clones or mass migration of primary tumor cells into axillary lymph nodes. This large‐scale integration of patient samples provides a high‐resolution map of cell diversity in normal and cancerous human breast. Synopsis To examine global changes in breast heterogeneity across different states, this gene expression resource integrates large‐scale patient samples from diverse tissue states and breast cancer subtypes, offering a refined high‐resolution map of cell diversity in the normal and cancerous human mammary gland. Single‐cell transcriptome analyses profile > 340,000 cells encompassing normal breast, preneoplastic BRCA1 +/– tissue, the major breast cancer subtypes, and metastatic lymph nodes. Pre‐ to post‐menopause transition is associated with marked stromal changes, with decreased PDGFRb and matrix‐associated genes in fibroblasts. Progression from preneoplasia to tumors correlates with increased immune infiltration in BRCA1 mutation carriers. Tumor epithelial compartments show comparable diversity in different breast cancer subtypes. Cycling CD8 + T‐cells are reduced in estrogen receptor (ER) + tumors, suggesting different immunoregulatory patterns. Both clonal selection and mass migration contribute to lymph node metastases in patients with ER + cancer. Graphical Abstract A large‐scale gene expression resource integrates diverse tissue samples and reveals unexpected heterogeneity of breast cancer subtypes.